Superimposed Pristine Limestone Aquifers with Marked Hydrochemical Differences Exhibit Distinct Fungal Communities - Nawaz, Ali; Purahong, Witoon; Lehmann, Robert; Herrmann, Martina; Küsel, Kirsten; Totsche, Kai U.; Buscot, François; Wubet, Tesfaye (Frontiers in Microbiology, 2016)
Fungi are one important group of eukaryotic microorganisms in a diverse range of ecosystems, but their diversity in groundwater ecosystems is largely unknown. We used DNA-based pyro-tag sequencing of the fungal internal transcribed spacer (ITS) rDNA gene to investigate the presence and community structure of fungi at different sampling sites of two superimposed limestone aquifers ranging from 8.5 to 84 m depth in the newly established Hainich Critical Zone Exploratory (Hainich CZE). We detected a diversity of fungal OTUs in groundwater samples of all sampling sites. The relative percentage abundance of Basidiomycota was higher in the upper aquifer assemblage, whilst Ascomycota dominated the lower one. In parallel to differences in the hydrochemistry we found distinct fungal communities at all sampling sites. Classification into functional groups revealed an overwhelming majority of saprotrophs. Finding taxa common to all analyzed groundwater sites, point to a groundwater specific fungal microbiome. The presence of different functional groups and, in particular plant and cattle pathogens that are not typical of subsurface habitats, suggests links between the surface and subsurface biogeosphere due to rapid transportation across the fracture networks typical of karstic regions during recharge episodes. However, further studies including sampling series extended in both time and space are necessary to confirm this hypothesis.